2004
DOI: 10.1007/s00415-004-0653-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and malformations of the human pyramidal tract

Abstract: The corticospinal tract develops over a rather long period of time, during which malformations involving this main central motor pathway may occur. In rodents, the spinal outgrowth of the corticospinal tract occurs entirely postnatally, but in primates largely prenatally. In mice, an increasing number of genes have been found to play a role during the development of the pyramidal tract. In experimentally studied mammals, initially a much larger part of the cerebral cortex sends axons to the spinal cord, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 137 publications
3
66
0
2
Order By: Relevance
“…The transcriptional mirroring between the spinal cord and hindbrain is broadly consistent with the well-established crossing over (decussation) of structure and function in the inferior hindbrain (42). Because the corticospinal tract only arrives at the inferior hindbrain by CS23 (17), any molecular asymmetry in descending axons would not be expected to affect the spinal cord directly, although it may affect the hindbrain by CS23. Therefore, in the spinal cord particularly, transcriptional asymmetry from CS13 to CS23 is likely to originate independently of top-down forebrain influences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional mirroring between the spinal cord and hindbrain is broadly consistent with the well-established crossing over (decussation) of structure and function in the inferior hindbrain (42). Because the corticospinal tract only arrives at the inferior hindbrain by CS23 (17), any molecular asymmetry in descending axons would not be expected to affect the spinal cord directly, although it may affect the hindbrain by CS23. Therefore, in the spinal cord particularly, transcriptional asymmetry from CS13 to CS23 is likely to originate independently of top-down forebrain influences.…”
Section: Discussionmentioning
confidence: 99%
“…One study, however, suggested that in 12-to 17-week-old fetuses the right cerebral cortex matures faster than the left one in terms of gene expression profiles (16). However, the corticospinal tract, which descends from the motor and somatosensory cerebral cortices to the spinal cord, only reaches the point of left-right crossover in the inferior hindbrain at 8 weeks postconception -the age of observed lateralization of arm movements-but does not yet extend into the spinal cord (17). Thus, lateralization of motor behavior at this stage is unlikely to reflect topdown asymmetry projected from the cerebral cortex.…”
mentioning
confidence: 99%
“…Aberrant wiring of neuronal circuits can lead to abnormal behavior and neurological disease (Jen et al, 2004;Ponnio and Conneely, 2004;ten Donkelaar et al, 2004). Left-right (L-R) differences in fiber tracts have been correlated with hemispheric specialization of the brain (Nucifora et al, 2005), and presumably underlie asymmetries in axonal connections.…”
Section: Development Of Correct Connections Between Neurons Is Cruciamentioning
confidence: 99%
“…At term, the deep structures we studied (portions of the corpus callosum and internal capsule) are still immature with respect to each of these cytologic and histologic features of WM [5]. Nevertheless, each deep WM structure is well established at this age, having been pioneered in the second trimester by long axonal projections arranged into relatively compact parallel bundles of axonal fascicles [29][30][31]. In contrast, the peripheral WM of the prefrontal and posterior parietal cortex that we sampled was much less developed at term, being only poorly myelinated and sparsely populated by associational fibers that have yet to establish widespread corticocortical connections [10,32].…”
Section: Status Of Cerebral Wm At Termmentioning
confidence: 99%